Pemikiran Fiqh al-Shafi'i: Telaah Atas Transformasi Qaul Qadim dan Qaul jadid - Ajat Sudrajat (Justicia Islamica, 2007)
This study aims to analyze the fiqh thought of Imam al-Shafi'i with a focus on the transformation between the Qaul Qadim (old opinion) and the Qaul Jadid (new opinion). This study explores the factors behind the change in Imam al-Shafi'i's views and their implications for the development of ushul fiqh. The method used is library research with a descriptive-analytical approach. The main sources of research include the works of Imam al-Shafi'i, such as Al-Risalah and Al-Umm, as well as academic studies that discuss changes in his legal methodology. The results of the study show that the transition from Qaul Qadim to Qaul Jadid was due to geographical factors, intellectual experience, and interaction with other schools of thought. This transformation reflects the flexibility of fiqh in responding to different contexts. This study emphasizes that al-Shafi'i's thinking remains relevant in the development of contextual Islamic law.